Committed emissions from existing energy infrastructure jeopardize 1.5 °C climate target - Tong, Dan (Nature, 2019)
Net anthropogenic CO(2) emissions must approach zero by mid-century to stabilize global mean temperature at the levels targeted by international efforts(1–5). Yet continued expansion of fossil fuel energy infrastructure implies already ‘committed’ future CO(2) emissions(6–13). Here we use detailed datasets of current fossil fuel-burning energy infrastructure in 2018 to estimate regional and sectoral patterns of “committed” CO(2) emissions, the sensitivity of such emissions to assumed operating lifetimes and schedules, and the economic value of associated infrastructure. We estimate that, if operated as historically, existing infrastructure will emit ~658 Gt CO(2) (ranging from 226 to 1479 Gt CO(2) depending on assumed lifetimes and utilization rates). More than half of these emissions are projected to come from the electricity sector, and infrastructure in China, the U.S.A., and the EU28 represent ~41%, ~9% and ~7% of the total, respectively. If built, proposed power plants (planned, permitted, or under construction) would emit an additional ~188 (37–427) Gt CO(2). Committed emissions from existing and proposed energy infrastructure (~846 Gt CO(2)) thus represent more than the entire carbon budget to limit mean warming to 1.5 °C with 50–66% probability (420–580 Gt CO(2))(5), and perhaps two-thirds of the budget required to similarly limit warming to below 2 °C (1170–1500 Gt CO(2))(5). The remaining carbon budget estimates are varied and nuanced(14,15), depending on the climate target and the availability of large-scale negative emissions(16), Nevertheless, our emission estimates suggest that little or no additional CO(2)-emitting infrastructure can be commissioned, and that earlier than historical infrastructure retirements (or retrofits with carbon capture and storage technology) may be necessary, in order meet Paris climate agreement goals(17). Based on asset value per ton of committed emissions, we estimate that the most cost-effective premature infrastructure retirements will be in the electricity and industry sectors, if non-emitting alternative technologies are available and affordable(4,18).